Fire birds : valuing natural wildfires and burned forests - Collard, Sneed B. (Bucking Horse Books, 2015)
Focusing on the work of University of Montana professor Richard Hutto, this book tells the story of how dozens of species of birds use the burn areas of wildfires. At least 15 bird species prefer burned forests to all other habitats.